2019 Open Doors report on international educational exchange — Any surprises?. Issue 11 (12th January 2020) - Dennis, Marguerite J.
Abstract : In 2018– 19, for the third year in a row, international student enrollment in American colleges and universities decreased at all academic levels, according to statistics published on Nov. 19, 2019, by the Institute of International Education, in collaboration with the United States Bureau of Educational and Cultural Affairs. Undergraduate students declined by 2.4%. Graduate student enrollment declined by 1.3%, and the number of international nondegree students declined by 5%. Only the numbers for Optional Practical Training increased, by 9.6% over the previous year.